The effect of positive autobiographical memory retrieval on decision-making under risk: A computational model-based analysis - Shimizu, Natsumi; Mochizuki, Yasuhiro; Chen, Chong; Hagiwara, Kosuke; Matsumoto, Karin; Oda, Yusuke; Hirotsu, Masako; Okabe, Emi; Matsubara, Toshio; Nakagawa, Shin (Frontiers in Psychiatry, 2022)
Psychiatric disorders such as depressive and anxiety disorders are associated with altered decision-making under risk. Recent advances in neuroeconomics and computational psychiatry have further discomposed risk-based decision-making into distinct cognitive computational constructs and showed that there may be disorder-specific alterations in these constructs. As a result, it has been suggested these cognitive computational constructs may serve as useful behavioral biomarkers for these disorders. However, to date, little is known about what psychological or behavioral interventions can help to reverse and manage the altered cognitive computational constructs underlying risk-based decision-making. In the present study, we set out to investigate whether recalling positive autobiographical memories may affect risk-based decision-making in healthy volunteers using a description-based task. Specifically, based on theories of behavioral economics, we dissected risk preference into two cognitive computational constructs, utility sensitivity and probability weighting. We found that compared to recalling neutral memories, retrieving positive autobiographical memories increased utility sensitivity (Cohen’s d = 0.447), indicating reduced risk aversion. Meanwhile, retrieving positive autobiographical memories also affected probability weighting (d = 0.377) such that subjects tended to overweight small probabilities while underweight large probabilities. Of clinical relevance, these changes were in the opposite direction compared to those reported in psychiatric disorders. These results argue for the potential therapeutic effect of positive autobiographical memory retrieval for the amendment of altered risk-based decision-making in psychiatric disorders.